Phosphatidylcholine Metabolism and ACAT Affect the Trafficking of LDL-derived Free Cholesterol in Cholesterol-loaded CHO Cells - Landry, Chandra (Université d'Ottawa / University of Ottawa, 2012)
In vitro studies have shown that the major membrane phospholipid phosphatidylcholine (PC) can positively influence the incorporation of cholesterol in lipid membranes. The influence of PC on the cellular trafficking of LDL-derived free cholesterol was investigated. Sterol regulatory-defective (SRD)-4 cells are Chinese hamster ovary (CHO)-derived fibroblasts that display vastly elevated rates for the synthesis and catabolism of PC. SRD-4 cells harbor two known gene mutations: a mutation in the functional allele for SCAP, resulting in defective feedback suppression of cholesterol biosynthesis; and a loss-of-function mutation in the functional allele for acyl-CoA:cholesterol acyl transferase (ACAT), an endoplasmic reticulum (ER)-localized enzyme that esterifies free cholesterol. Incubation of SRD-4 cells with 50 µg/ml low density lipoprotein (LDL) for 18 h resulted in lysosomal accumulation of free cholesterol as revealed by filipin staining. This accumulation was not evident following LDL treatment of parental CHO7 cells, and was blunted in SRD-2 cells that express a constitutively-active form of SREBP-2 and overproduce cholesterol but have functional ACAT activity. Treatment of SRD-2 cells with LDL in the presence of an ACAT inhibitor 58-035 resulted in robust lysosomal cholesterol accumulation that was reversible upon drug washout, supporting that cholesterol trafficking in cholesterol-loaded cells is dependent on ACAT activity and, more specifically, ER free cholesterol levels. Lysosomal accumulation of LDL-derived cholesterol was prevented in SRD-4 cells supplemented with lyso-PC (50 µM), a substrate for PC synthesis through the reacylation pathway, and also in cells treated with bromoenol lactone (BEL), an inhibitor of phospholipase A2 implicated in bulk PC turnover. In a counter study, lysosomal LDL-derived cholesterol accumulation was induced in parental CHO-7 cells using R-propranolol, which inhibits the conversion of phosphatidic acid to diacylglycerol (DAG), a substrate in the CDP-choline pathway. This blockage was also relieved through co-treatment with lyso-PC. These studies support that PC to free cholesterol ratios in downstream organellar membranes can influence cholesterol trafficking out of lysosomal compartments in cholesterol-loaded cells.
Keywords: Cholesterol; Filipin; NPC1; LDLR; Phosphatitylcholine; Lysosomal Loading; Lipid Droplet